DAYA TETAS TELUR NYAMUK Aedes aegypti PADA TIGA JENIS AIR PERINDUKAN DI KELURAHAN MEDONO KOTA PEKALONGAN - Tuti Suparyati; Muhammad Daniful Himam (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2021)
The Aedes aegypti mosquito lays its eggs in calm and clear water. People often collect water for daily needs which is placed outside or inside the house, water comes from tap water, rainwater, and well water, provide a good place for Aedes aegypti to breed. The Aedes aegypti as a vector of the Dengue Virus and others. The prevalence of Dengue Fever in Pekalongan City in 2017, as many as 44 cases of DHF in the Medono Community Health Center area. The purpose of this study was to determine the hatchability of Aedes aegypti eggs in the well water, tap water, and rainwater in Medono Village, Pekalongan City. The research was carried out at the Research and Development Center for Disease Vector and Reservoir Research Laboratory (B2P2VRP) Salatiga. The sample consisted of 540 eggs of Aedes aegypti. This research is descriptive, which makes observations and examinations in the laboratory by inserting Aedes aegypti eggs into three types of water, with nine replications for each type of water, each glass filled with 20 mosquito eggs, and observed for 24 hours. Research also measures water temperature and pH. The results show the average number of mosquito eggs hatched in well water as many as 6.89 (34.45%), rainwater 4.44 (22.2%), and tap water 2.67 (13.35%). The pH of the well water is 7.56, rainwater is 7, and tap water is 6. The temperature of the three types of water is the same, which is 25O C. The conclusion of this research is the hatchability of Aedes aegypti eggs in well water as many as 6.89 (34.45%), rainwater 4.44 (22.2%) and tap water 2.67 (13.35%). Tap water with a lower pH has a lower hatchability of Aedes aegypti eggs.